Hydrothermal Identification Based on Rock Resistivity Value Using Dipole-dipole Configuration Geoelectric Method In Lemeu Village, Lebong Regency, Bengkulu Province: Ripal Zamrawi, Suhendra Suhendra, Halauddin Halauddin, Rendoza Rendoza, Aisyah Cindy Phylia Putri, Usman Gumanty, Wahyu Cahyadi Setiawan - Ripal Zamrawi Zamrawi; Suhendra Suhendra; Halauddin, Rendoza Rendoza; Aisyah Cindy Phylia Putri Phylia Putri; Usman Gumanty Gumanty; Wahyu Cahyadi Setiawan Setiawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
Geothermal potential is identical to the presence of volcanoes as reservoir sources, but hydrothermal sources are rarely found in places that are not associated with volcanoes and faults. One of the areas where there is a hydrothermal system located in Lemeu Village has not yet been studied. This research was conducted in November 2023 and data collection was carried out around the hot springs of Lemeu Village, Lebong Regency, Bengkulu Province.